Risk Factors for Colonization With Multidrug‐Resistant Bacteria Among Patients Admitted to the Intensive Care Unit After Returning From Abroad. Issue 5 (17th June 2015) - Angue, Marion; Allou, Nicolas; Belmonte, Olivier; Lefort, Yannick; Lugagne, Nathalie; Vandroux, David; Montravers, Philippe; Allyn, Jérôme
Abstract : Background: Few national recommendations exist on management of patients returning from abroad and all focus on hospitalized patients. Our purpose was to compare, in an intensive care unit (ICU), the admission prevalence and acquisition of multidrug‐resistant (MDR) bacteria carriage in patients with ("Abroad") or without ("Local") a recent stay abroad, and then identify the risk factors in "Abroad" patients. Methods: In this retrospective study, we reviewed charts of all the patients hospitalized in the ICU unit from January 2011 through July 2013 with hygiene samplings performed. We identified all patients who had stayed abroad ("Abroad") within 6 months prior to ICU admission. Results: Of 1, 842 ICU patients, 129 (7%) "Abroad" patients were reported. In the "Abroad" group, the rate of MDR strain carriage was higher at admission (33% vs 6.7%, p  < 0.001) and also more often diagnosed during the ICU stay (acquisition rate: 17% vs 5.2%, p  < 0.001) than in "Local" patients. Risk factors associated with MDR bacteria carriage at admission in "Abroad" patients were diabetes mellitus [odds ratio (OR) 5.1 (1.7–14.8), p  = 0.003] and "hospitalization abroad with antibiotic treatment" [OR 10.7 (4.2–27.3), p  < 0.001]. Hospitalization abroad without antibiotic treatment was not identified as a risk factor. Conclusions: The main factor associated with MDR bacteria carriage after a stay abroad seems to be a hospitalization abroad only in case of antibiotic treatment abroad. Screening and isolation of "Abroad" patients should be recommended, even in case of a first negative screening.